MODEL KOMUNIKASI PELAYANAN PUBLIK AKADEMIK DI SLB NEGERI A KOTA BANDUNG - Amida Windari Fitria; Hanny Hafiar; Centurion C. Priyatna (Universitas Merdeka Malang, 2019)
Abstract Public service is one of the activities that must be carried out by the institution properly. Every institution, including schools, has internal and external publics that need to be served. One of the external publics for SLBN A in Bandung City is the academic public who conducts research, service, and teaching practice for SLB teacher candidates. The intensity of academic public visits is quite high, so excellent public service communication is needed. The purpose of this study was to determine the communication model of academic public service in SLB Negeri A Bandung City. The method used is exploratory case study, with a single case. Data collected by interview, observation and literacy tracking. The informants were chosen purposively consisting of management at the school, teachers, students, parents of students, alumni, and also the academic public itself. The results show that: communicators or parties providing services to the academic public are Administrative, Public Relations, School Principals, RD Coordinators and Teachers. The message conveyed is about the communication procedures in academic public services which have seven stages. The media used are face-to-face communication (formal and informal) and media communication (Whatsapp, Telephone, Correspondence and Disposition). The communicant is an academic public including students, lecturers, researchers and observers who carry out the PPL / PPG / PKL program, final research (thesis, thesis and dissertation), non-final research (grants and projects). Academic public feedback is carried out by providing research reports to SLBN A Bandung. Keywords: communication model, public service, academic public, SLBN A Bandung.DOI: https://doi.org/10.26905/nomosleca.v5i2.3442